2022
DOI: 10.32871/rmrj.2109.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Management: Pre-pandemic, Pandemic and Beyond

Abstract: The pandemic disrupts the functioning of most sectors and exposes the shortcomings and vulnerabilities among many. Literature search in leading databases reveals that though shocked by the crisis, many industries and organizations have reinvented themselves through various strategies to overcome the consequences of the pandemic. After a thorough analysis of individual articles, the authors found out that human resource management considers the disruptive changes in the working pattern, challenges, and opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…However, it was concluded that positive HRM strategies during COVID-19 increased the organizational productivity, which had an indirect association with the employees' performances, motivation, mental well-being, productivity and satisfaction. − Post COVID-19: Several authors like [44,[134][135][136][137] studied the practice of incorporating more IT tools and ISs by the HR as a part of the working culture post-COVID-19.…”
Section: Comparative Analysismentioning
confidence: 99%
“…However, it was concluded that positive HRM strategies during COVID-19 increased the organizational productivity, which had an indirect association with the employees' performances, motivation, mental well-being, productivity and satisfaction. − Post COVID-19: Several authors like [44,[134][135][136][137] studied the practice of incorporating more IT tools and ISs by the HR as a part of the working culture post-COVID-19.…”
Section: Comparative Analysismentioning
confidence: 99%